Kupyaphores are zinc homeostatic metallophores required for colonization of Mycobacterium tuberculosis - Mehdiratta, Kritee; Singh, Shubham; Sharma, Sachin; Bhosale, Rashmi S.; Choudhury, Rahul; Masal, Dattatraya P.; Manocha, Alzu; Dhamale, Bhushan Dilip; Khan, Naseem; Asokachandran, Vivekanand; Sharma, Pooja; Ikeh, Melanie; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Mycobacterium tuberculosis (Mtb) endures a combination of metal scarcity and toxicity throughout the human infection cycle, contributing to complex clinical manifestations. Pathogens counteract this paradoxical dysmetallostasis by producing specialized metal trafficking systems. Capture of extracellular metal by siderophores is a widely accepted mode of iron acquisition, and Mtb iron-chelating siderophores, mycobactin, have been known since 1965. Currently, it is not known whether Mtb produces zinc scavenging molecules. Here, we characterize low-molecular-weight zinc-binding compounds secreted and imported by Mtb for zinc acquisition. These molecules, termed kupyaphores, are produced by a 10.8 kbp biosynthetic cluster and consists of a dipeptide core of ornithine and phenylalaninol, where amino groups are acylated with isonitrilecontaining fatty acyl chains. Kupyaphores are stringently regulated and support Mtb survival under both nutritional deprivation and intoxication conditions. A kupyaphore-deficient Mtb strain is unable to mobilize sufficient zinc and shows reduced fitness upon infection. We observed early induction of kupyaphores in Mtb-infected mice lungs after infection, and these metabolites disappeared after 2 wk. Furthermore, we identify an Mtb-encoded isonitrile hydratase, which can possibly mediate intracellular zinc release through covalent modification of the isonitrile group of kupyaphores. Mtb clinical strains also produce kupyaphores during early passages. Our study thus uncovers a previously unknown zinc acquisition strategy of Mtb that could modulate host-pathogen interactions and disease outcome.
Keywords: metallophore; nutritional immunity; tuberculosis; zinc